Biochemical and structural investigation of two paralogous glycoside hydrolases from Zobellia galactanivorans: novel insights into the evolution, dimerization plasticity and catalytic mechanism of the GH117 family. (1st February 2015) - Ficko‐Blean, Elizabeth; Duffieux, Delphine; Rebuffet, Étienne; Larocque, Robert; Groisillier, Agnes; Michel, Gurvan; Czjzek, Mirjam
<x xml:space="preserve">Abstract</x> The family 117 glycoside hydrolase (GH117) enzymes have exo‐α‐1, 3‐(3, 6‐anhydro)‐L‐galactosidase activity, removing terminal nonreducing α‐1, 3‐linked 3, 6‐anhydro‐L‐galactose residues from their red algal neoagarose substrate. These enzymes have previously been phylogenetically divided into clades, and only the clade A enzymes have been experimentally studied to date. The investigation of two GH117 enzymes, Zg3615 and Zg3597, produced by the marine bacterium Zobellia galactanivorans reveals structural, biochemical and further phylogenetic diversity between clades. A product complex with the unusual β‐3, 6‐anhydro‐L‐galactose residue sheds light on the inverting catalytic mechanism of the GH117 enzymes as well as the structure of this unique sugar produced by hydrolysis of the agarophyte red algal cell wall.